Explaining innovative activity in service industries: Micro data evidence for Switzerland - Spyros Arvanitis (ETH Zurich, KOF Swiss Economic Institute, 2002)
In earlier work we analyzed empirically the innovative behaviour of Swiss manufacturing firms building on the wide consent in economic literature that demand prospects, type and intensity of competition, market structure, factors governing the production of knowledge (appropriability, technological opportunities), innovation and production costs as well as firm size are the main determinants of a firm's innovative activity. In this paper we applied the same model to analyze innovative activities in the service sector. Several innovation variables referring to the input as well as the output side of the innovation process served as endogenous variables of the innovation model. For the empirical work we used firm data from nine service industries collected by the Swiss Innovation Survey 1999 which was based on a questionnaire practically identical with that of the Innovation Surveys of the European Community. We obtained a pattern of explanation of the innovative activity which looked quite plausilble across the different types of innovation measures used (input-oriented and output-oriented innovation variables); it was also consistent to that found earlier for manufacturing. In general, the theoretical model captured rather the characteristics of the basic decision to innovate rather than those of the desicion to choose some level of innovative activity.
Keywords: 330; Dienstleistungssektor; Innovation; Schätzung; Schweiz